Serum Metabolomic Profiling Reveals the Amelioration Effect of Methotrexate on Imiquimod-Induced Psoriasis in Mouse - Jiaxin Zong; Jieyi Cheng; Jieyi Cheng; Yuanfeng Fu; Jing Song; Weisong Pan; Li Yang; Ting Zhang; Mingmei Zhou (Frontiers Media S.A., 2020)
Background:The imiquimod (IMQ)-induced psoriasis mouse model has been used as a model for pathogenic mechanism research, and methotrexate (MTX) is widely employed to treat various clinical manifestations of psoriasis. We explored the underlying pathogenesis of psoriasis and the treatment mechanism of the conventional drugs from the metabolic perspective of the psoriasis mouse model.Methods:Male BALB/c mice were smeared IMQ for 7 days to induce treatment-resistant psoriasis and intragastrically administered 1 mg/kg MTX. We evaluated inflammation of psoriasis-like lesions and therapeutic effects of MTX based on histological changes and immunohistochemistry. Based on gas chromatography-mass spectrometer detection of serum samples, a comprehensive metabolomics analysis was carried out to identify alterations of metabolites.Results:It was found that MTX ameliorated psoriatic lesions (representative erythema, scaling, and thickening) by inhibiting proliferation and differentiation of keratinocytes. Using multivariate statistical analysis to process metabolomics data, the results displayed alterations in serum metabolites among mice of the control group, IMQ group, and MTX group. Compared with group, psoriasis mice had the higher level of d-galactose and lower expression of myo-inositol, 9,12-octadecadienoic acid, and cholesterol. In contrast with the model set, serum levels of glycine, pyrrolidone carboxylic acid, d-galactose, and d-mannose were significantly decreased in the MTX group.Conclusion:The differential metabolites, reflecting the perturbation in the pathways of inositol phosphate metabolism; galactose metabolism; glyoxylate and dicarboxylate metabolism; glycine, serine, and threonine metabolism; and glutathione metabolism, may lead to the pathogenesis of psoriasis, and they are also related to the pharmacological treatment effect of MTX on psoriasis. This study established the foundation for further research on the mechanism and therapeutic targets of psoriasis.